Impact of prophylaxis, inhibitors, and genetics on joint outcomes according to the IPSG-MRI score in hemophilia A, B and vWD type 3 - Seeliger, Anna; Berg, Sebastian; Glonnegger, Hannah; Boeckelmann, Doris; Uhl, Markus; Oldenburg, Johannes; Schlagenhauf, Axel; Zieger, Barbara (Frontiers in Medicine, 2026)
IntroductionHemophilia A (HA) and hemophilia B (HB) are X-linked-bleeding disorders caused by deficiency of clotting factors VIII and IX, while von Willebrand disease (vWD) type 3 involves the lack of von Willebrand factor and FVIII. Chronic joint damage from recurrent bleeding is a serious complication.AimThe aim was to investigate the association of prophylactical treatment, severity of the disease and joint outcome.MethodsIn this retrospective, single-center study we evaluated joint health in 41 patients with HA, HB, and vWD type 3 who visited our outpatient clinic since 2000 using Magnetic resonance imaging (MRI) and applied the International Prophylaxis Study Group (IPSG) score. A total of 246 MRI images (knees, elbows, ankles) were analyzed in relation to disease severity, genetics, inhibitor-formation, and therapy.ResultsOf 41 patients, 28 (68%) had severe HA or HB, 10 (24%) moderate, one (2%) mild, and two (5%) were vWD patients. 19 patients with severe HA/HB received primary prophylaxis. Inhibitors developed in 7 patients (17%), most of them had loss-of-function mutations. We observed hemophilic arthropathy in 7/39 (18%) hemophilia patients (all with severe HA/HB). Only one of the 19 patients receiving early prophylaxis developed arthropathy, in the context of inhibitor development. Minor changes (IPSG score 1–5) were observed in 20% of joints while 74% of joints showed no alterations (IPSG score 0). Only 6% of joints showed hemophilic arthropathy (IPSG score ≥ 8) with ankle joints most frequently affected (10%). Among vWD-patients, one exhibited minor changes; the other had no detectable joint damage despite vWF-inhibitor presence.DiscussionThis study shows that the IPSG score is a suitable tool for assessing joint health in patients with hemophilia and vWD. Reduced joint damage was associated with early diagnosis, consistent prophylaxis, and therapy adherence.